Ukrainian adaptation of the Flourishing scale - VELDBREKHT, Olena; RYBACHOK, Daryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. The Flourishing Scale developed by E. Diener is based on a contemporary concept of psychosocial well-being that includes eight components: purpose and meaning in life, supportive relationships, engagement, competence, self-acceptance, optimism, contributing to the well-being of others, and being respected by others. The adaptation of this tool will be a useful contribution to Ukrainian psychological science and practice. Methods. The adaptation procedure was carried out in accordance with the guidelines of the International Test Commission. The study was conducted in four waves during 2024-2025. The sample comprised 1,254 participants aged 10 to 82 (M = 27.3, SD = 12.8). The majority of respondents were women (77.3%). Results. The adapted scale demonstrated high internal consistency (Cronbach’s α = 0.88, Spearman-Brown split-half coefficient = 0.87). Confirmatory and exploratory factor analyses supported a unidimensional factor structure, consistent with the theoretical model. Test–retest reliability was assessed in a student subsample (n = 25) with an 8-week interval; the correlation between two measurements was r = 0.55, which indicates the stability of the measured characteristic. Convergent validity was confirmed by the expected positive correlations between the flourishing score and related psychological constructs, including life satisfaction, all PERMA components (positive emotions, engagement, relationships, meaning, and achievement), self-worth, purposefulness, self-efficacy, and perceived interpersonal support. At the same time, significant negative correlations were observed with parameters of anxiety, depression, and war-related stress reactions. The mean score on the Flourishing Scale in the sample was 41.56 (SD = 8.15) with a positively skewed distribution. The survey results are not related to age or gender. Conclusions. The Ukrainian adapted version of the Flourishing Scale is an effective instrument for the general assessment of positive personality functioning. The scale will be useful for scientific research, educational and therapeutic practice.